Factors Associated with Knowledge of Pregnancy Danger Signs and Antenatal Care Compliance: A Cross-Sectional Study - S, R.Oktaviance.; Bangun, Seri Rayani; Sinaga, Desriati; Veronika, Anita; Martini, Sri (Journal of Applied Nursing and Health, 2026)
Background: Adequate knowledge of pregnancy danger signs plays a critical role in promoting antenatal care (ANC) compliance. Poor adherence to ANC visits remains a significant contributor to preventable maternal complications. Research aimed to analyze the association between maternal knowledge of pregnancy danger signs and ANC compliance and to identify the most dominant predictors. Methods: An analytical cross-sectional study was conducted among 249 pregnant women. Participants were selected using purposive sampling. Data were collected through structured questionnaire-based interviews and verification of ANC visits using medical records and Maternal and Child Health (MCH) books. Bivariate associations were tested using the Chi-square test. Variables with p < 0.25 were included in a multiple logistic regression analysis. Statistical significance was set at p < 0.05. Results: Of the respondents, 55.0% were aged <27 years, 57.0% had education below junior high school, 56.6% were primigravida, and 55.4% lived within 5 km of a health facility. ANC compliance was observed in 55.8% of participants, while 55.8% demonstrated low knowledge of pregnancy danger signs. Bivariate analysis showed significant associations between ANC compliance and maternal age, educational methods, motivation, attitude, parity, distance to health facility, and knowledge (all p = 0.001). Multivariate analysis identified knowledge as the strongest predictor of ANC compliance (p = 0.019; OR = 3.380; 95% CI: 1.222–9.348), adjusted for maternal age (p = 0.048). Conclusion: Maternal knowledge of pregnancy danger signs is the most influential factor associated with ANC compliance. Strengthening targeted health education strategies may improve maternal service utilization.